English Fun Games : Meningkatkan Motivasi Dan Kemampuan Berbahasa Inggris Anak - Anak Di Desa Ketapi, Tanjung Agung Palik Bengkulu Utara - Suryani, Herma; Nurkhalisa, Nabila; Manihuruk, Rifkah; Amaliah, Kiki; Lody, Muhammad Afif; Pranata, Carles Yudha; Lovetha, Nindya Laura (Universitas Negeri Padang, 2024)
Kuliah Kerja Nyata Tematik (KKNT) is a program that students in tertiary institutions must take to provide them as intellectual candidates with practical experience to increase sensitivity and concern for situations and conditions as well as problems facing society so that it becomes a value in pursuing education at tertiary institutions, which in The implementation has two mandatory work programs, namely Micro, Small and Medium Enterprises (MSMEs) and Tourism as well as a minimum of three additional work programs. In this research we highlight an additional work program, namely a work program in the field of education, namely the importance of learning English. In this work program, problems were found regarding the lack of limited schools in Ketapi Village and the lack of fun methods for learning English for children in Ketapi Village. This activity was carried out at the Secretariat of Group 55 KKNT, Bengkulu University. This work program has five stages with each different theme, namely Greetings and Farewell, Self-Introduction, Fruits, Body Parts, and End Game. This activity is important because children have the opportunity to learn English and children are more enthusiastic in learning English to understand English learning through various interesting learning methods such as the Flashcard method and singing a song. Based on the activities that have been carried out, it can be concluded that: 1. Ketapi Village children can understand various English language lessons. 2. Ketapi Village children can apply the English learning methods they have learned previously.